Determination of Trace Bismuth in Environmental Waters by ICP‐MS with Cobalt Ion‐Assisted Photochemical Vapour Generation. Issue 3 (8th May 2020) - Yu, Ying; Zhao, Qian; Bao, Haolin; Mou, Qing; Shi, Zeming; Chen, Youliang; Gao, Ying
Abstract : With increasing use of bismuth in industry, a better understanding of its environmental behaviour is required, including an improved knowledge of its background concentration range in (non‐saline) freshwaters. However, the poor analytical sensitivity of previous methods may lead to inaccurate measurement results for Bi 3+ in environmental samples. In this work, cobalt ion‐assisted photochemical vapour generation (PVG) was developed for the detection of trace Bi with inductively coupled plasma‐mass spectrometry (ICP‐MS) measurement. The volatile species of Bi was found to be (CH3 )3 Bi generated under UV irradiation in the presence of formic acid, acetic acid and Co 2+ . The major parameters potentially influencing the detection of Bi were investigated. Under optimised conditions, the limit of detection (3 s, n = 11) of the proposed method was 0.3 ng l −1 . The analytical sensitivity was enhanced about 70‐fold for Bi 3+ compared with that using classic pneumatic nebulisation of ICP‐MS. Furthermore, the proposed method showed better analytical sensitivity and anti‐interference ability towards co‐existing ions compared with ferric ion‐assisted PVG systems. The accuracy of the proposed method was evaluated by analysis of environmental water samples and certified reference materials with satisfactory results. Key Points: Cobalt ion‐assisted photochemical vapour generation was developed for the determination of trace bismuth with ICP‐MS. The method is simple and sensitive. The volatile species of Bi was found to be (CH3 )3 Bi during the photochemical vapour generation.